MODERN CHALLENGES TO THE NON-PROLIFERATION REGIME AND TRANSFORMATION OF THE CONTROL ARCHITECTURE IN THE POST-NEW START ERA - Myronenko, Vyacheslav (Public Management and Policy, 2025)
The contemporary framework of global nuclear security faces a severe institutional instability, resulting from the breakdown of core mechanisms for strategic oversight. The effective disintegration of these pacts, the establishment of cross-regional networks for illicit nuclear technology transfer (such as the Iran – Democratic People’s Republic of Korea – Russia chain), and the conversion of nuclear pressure into a diplomatic tool have substantially amplified the threat of worldwide destabilization. The conventional oversight scheme, reliant on diplomatic statements, field verifications, and decision-blocking via veto in the UN Security Council, has revealed its susceptibility to intentional abuses, rapid technological advancements, and tactics of status-quo challengers evading joint pressure. To overcome these barriers, the article outlines theoretical foundations for upgrading the oversight system through evolution from an outdated diplomatic model to an integrated techno-legal structure. This updated scheme incorporates three primary elements: automated surveillance employing artificial intelligence, open-source intelligence, and space-based systems for detecting deviations and breaches; reinforcement of the safeguards regime via distributed databases (blockchain) to guarantee the integrity and openness of nuclear resource supply chains; the concept of automatic accountability activators – policy-independent legal tools that trigger sanctions automatically upon breach verification, circumventing veto in the United Nations Security Council. The study examines the dynamics of nuclear deterrence ideas, highlights flaws in standard verification methods, and analyzes potential hazards of delegating decisions in nuclear management, control, and communication to AI algorithms. Drawing on a synthesis of adherence experiences in mass destruction weapon limitation spheres, it argues for a multilevel restraint structure capable of neutralizing chain arms races and branched channels of nuclear material dissemination. The proposed integrated structure is designed to revive mutual confidence, foreseeability, and preemptive resilience in a multipolar reality by forming a neutral, prompt, and open response apparatus, free from individual countries’ influence. The research enriches theoretical and practical comprehension of the forthcoming phase in nuclear diplomacy, where genuine protection relies on the interplay of international law norms, innovative technologies, and institutional autonomy.